The Bickerdike-Robinson-Lerner condition and the dynamics of the real exchange rate - Brito, Paulo (2021)
This paper presents a dynamic general equilibrium model of the real exchange rate for a semi-small open economy, within the Obstfeld-Svensson-Raziu tradition. The dynamics of the real exchange rate is determined jointly with the dynamics of capital accumulation and external debt, in a neoclassical economy with intertemporally independent preferences. Two main features of the model are shown to be crucial for the comparative dynamics results: a Bickerdicke-Robinson-Lerner condition and the consideration of imports of foreign goods for investment. If there are no imports for investment then shocks in the fundamentals (productivity and autonomous external demand) will imply a short run appreciation of the real exchange rate followed by a trajectory of depreciation. If there are imports for investment, the short run response of the total real investment is larger and will behave as a substitute for later increases in the capital stock. This implies that the behavior of the model will tend to be ambiguous.